Yield and nutrient uptake of safflower as influenced by different varieties and nitrogen levels under irrigated and rainfed condition - Hitesh Genan; V. G. Bavalgave; Anuj Kumar; Rohitash Doodwal; Inshita Gupta (Annals of Agricultural Research, 2024)
A field experiment was carried out to study the “Response of safflower varieties to different nitrogen levels under irrigated and rainfed condition” at College Farm, N. M. College of Agriculture, Navsari Agricultural University, Navsari during rabi 2022-23. The experiment comprised with sixteen treatments consisting irrigation conditions (I1-irrigated and I2- rainfed) and four levels of nitrogen (N1- 0 kg N ha-1, N2- 30 kg N ha-1, N3- 60 kg N ha-1 and N4- 90 kg N ha-1) as main plot treatment and two varieties (V1-PBNS- 12 and V2- PBNS- 86) in sub-plot with three replications in a split-split plot design. The results revealed that the seed yield (1466 kg ha-1), stover yield (3300 kg ha-1), nutrient content (only N content in seed)-uptake and available nutrients in soil after harvest recorded significantly superior under irrigated condition as compare to rainfed condition. Among the different levels of nitrogen application, the seed yield (1490 kg ha-1), stover yield (3278 kg ha-1), nutrient content (only N content in seed and stover both)-uptake and available nutrients in soil after harvest were recorded significantly superior with the application of 90 kg N ha-1. In case of variety, the seed yield (1302 kg ha-1), stover yield (2972 kg ha-1), nutrient content (only N content in seed)-uptake and available nutrients in soil after harvest (only K2O) were recorded significantly superior in variety PBNS-12 than PBNS-86.